2016
DOI: 10.1007/s12035-016-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cell Cycle and Up-Regulation of Neuronal Markers During SH-SY5Y Neurodifferentiation by Retinoic Acid are Mediated by Reactive Species Production and Oxidative Stress

Abstract: Human neuroblastoma SH-SY5Y cells have been used as an in vitro model for neurodegenerative disorders such as Parkinson's disease and can be induced to a mature neuronal phenotype through retinoic acid (RA) differentiation. However, mechanisms of RA-induced differentiation remain unclear. Here, we investigate the role of reactive species (RS) on SH-SY5Y neuroblastoma cells under RA differentiation, using the antioxidant Trolox® as co-treatment. We found that RA treatment for 7 days reduced the cell number and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…SH-SY5Y are neuroblast-like cells that can be differentiated into a mature neuronal phenotype using several differentiating agents, including RA, phorbol esters, and neurotrophins (Kovalevich & Langford, 2013). Cells under RA treatment have shown to develop long and extensively branched neurites, express neuronal cell markers (NeuN, tyrosine hydroxylase, neuron specific enolase, synaptophysin, post-synaptic associated protein-97, and β-III tubulin) (Cheung et al, 2009;Kunzler et al, 2017;Lopes et al, 2010), and exhibit mature excitability (Toselli, Tosetti, & Taglietti, 1996;Tosetti, Taglietti, & Toselli, 1998). We observed an alteration in cell morphology, as well as an increase in NeuN levels (a marker for mature neurons) after RA treatment, as previously reported (Cheung et al, 2009;Lopes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y are neuroblast-like cells that can be differentiated into a mature neuronal phenotype using several differentiating agents, including RA, phorbol esters, and neurotrophins (Kovalevich & Langford, 2013). Cells under RA treatment have shown to develop long and extensively branched neurites, express neuronal cell markers (NeuN, tyrosine hydroxylase, neuron specific enolase, synaptophysin, post-synaptic associated protein-97, and β-III tubulin) (Cheung et al, 2009;Kunzler et al, 2017;Lopes et al, 2010), and exhibit mature excitability (Toselli, Tosetti, & Taglietti, 1996;Tosetti, Taglietti, & Toselli, 1998). We observed an alteration in cell morphology, as well as an increase in NeuN levels (a marker for mature neurons) after RA treatment, as previously reported (Cheung et al, 2009;Lopes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There are many lines of evidence showing the effect of RA-differentiation in SH-SY5Y regarding the evaluation of proliferation rates (Ross 1996;Pezzini et al 2016;Kunzler et al 2016). Previous studies have demonstrated that RAinduced differentiation can cause cell cycle arrest either in G1/G0 phase or in G2/M phase and a decrease in proliferation rates, which leads to terminal differentiation of neuroblastoma cells (Qiao et al 2012;Hämmerle et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrate that proliferative neuronal stem cells have high ROS levels, which is required for self-renewal and neurogenesis with underlying PI3-K/Akt signaling [ 45 ]. A significant increase in the differentiation markers (PI3-K/Akt and MAP-K/ERK) was found in differentiated SH-SY5Y compared to undifferentiated cells indicating that these kinases are involved in neuronal differentiation [ 46 ]. This finding is corroborating previously published data [ 5 ] and other studies also demonstrated that the PI3-K/Akt improved neurite elongation in primary hippocampal and cortical neurons [ 21 , 22 , 47 ].…”
Section: Neuronal Differentiationmentioning
confidence: 99%